Thermal Field Monitoring When Exposing Soft Tissues to Low Temperatures: Thermography Prospects and Limitations - Kovalov, Gennadiy; Chyzh, Mykola; Globa, Vyacheslav; Shustakova, Galyna; Fomenko, Yuliya; Gordiyenko, Eduard (Problems of Cryobiology and Cryomedicine, 2024)
The review analyzes the existing tools for monitoring the dynamics of thermal fi elds when exposing the soft tissues to low temperatures. Features of contact and non-contact temperature measurements have been considered, their capabilities and limitations have been noted. There was substantiated the need to develop the procedures of intra-operative temperature control. Special attention has been paid to the non-contact non-invasive infrared thermography. This method has been shown to be applied for intra-operative monitoring of the movement of the ice lump edge on the surface of tissues, detection of a disordered thermal symmetry of the ice spot, thermal fi eld dynamics on the surface of tissues inside and outside the area of the operative zone. However, thermal imaging control of the dynamics of the primary necrosis zone and the ice ball edge in the volume of tissues is possible only under certain parameters of cryoimpact, for example, with a short-term cooling of tissues with a quasi-point nitrogen cryoapplicator. The possibility of using thermography at other stages of cryosurgery is also considered, i. e. as the method of additional diagnosis at the stage of surgery planning, as well as during the post-surgery period to control healing, scarring, etc. Probl Cryobiol Cryomed 2024; 34(1):003–018